N‐doped TiO2/s‐PS aerogels for photocatalytic degradation of organic dyes in wastewater under visible light irradiation. Issue 8 (7th April 2014) - Vaiano, Vincenzo; Sacco, Olga; Sannino, Diana; Ciambelli, Paolo; Longo, Simona; Venditto, Vincenzo; Guerra, Gaetano
Abstract BACKGROUND Heterogeneous photocatalysis for the degradation of non‐biodegradable organic contaminants in wastewater is an alternative to traditional treatment techniques. Since the applications developed employ photocatalysts in powder form, a main disadvantage remains related to the recovery of photocatalysts from the treated wastewater, resulting in damage and shorter lifetime for the recirculation pumps. Structured photocatalysts offer a valid solution to simplify the process; however, they have to guarantee light transmission, long‐term stability under different operating conditions and under mechanical stress. RESULTS The photocatalytic performances of N‐doped TiO2 nanocomposite syndiotactic polystyrene aerogels (Nt‐sPS) were analyzed in the presence of visible light. A widely used model pollutant, methylene blue (MB), was chosen to verify the photocatalytic performance. After about 180 min of irradiation, on Nt‐sPS, the conversion of MB reached 30%, higher than that obtained (16%) when the photocatalyst is suspended as powder in the liquid reaction medium. CONCLUSION N‐doped TiO2, obtained by direct nitration during the hydrolysis of titanium tetraisopropoxide with ammonia solutions, was immobilized in s‐PS aerogels, yielding high activity in the removal of methylene blue under visible light irradiation, in comparison with N‐doped TiO2 dispersed as powder in solution. © 2014 Society of Chemical Industry